The Influence of Promotion, Price, and Trust on Customer Satisfaction Levels on the Lazada E-commerce Platform in Bekasi City - Muhammad Rianda (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research aims to examine the influence ofPromotion, Price, and Trust on Customer SatisfactionLevels. This research focuses on a literature reviewthat designs future research plans. The researchobject will be Customer Satisfaction from Lazada Ecommerce Platform users. This research wasconducted in Bekasi City using a quantitative researchapproach where the population in this study was notknown with certainty so it used the assessmentapproach from Hair et al. This research will use SPSS28 statistical tools to test research data.